Assessment of the mechanical properties and antimicrobial efficiency of orthodontic adhesive modified with Salvadora Persica oil - Ameer Abdulhaddi; Sarmad S. Salih. Al Qassar; Ahmed Mudhfar Mohammed (Romanian Journal of Stomatology)
Objectives. This study examines the mechanical properties and antimicrobial effectiveness of orthodontic adhesive enhanced with Salvadora persica (SP) oil. It includes assessments of adhesive remnant index (ARI), shear bond strength (SBS), and evaluates its antimicrobial efficacy against Streptococcus mutans. Methods. Forty freshly extracted human premolars were included in the study. These teeth were thoroughly cleaned, polished, and rinsed with water before drying. Following this, the buccal surfaces were etched using 37% phosphoric acid gel. Standard stainless steel orthodontic brackets were used in the study. The brackets were bonded using (Heliosit, Ivoclar, Zurich, Switzerland) orthodontic adhesive in four distinct groups: a control group was established wherein bonding occurred without any adhesive modification, alongside three experimental groups wherein Salvadora persica oil was integrated into the adhesive at concentrations of 1%, 3%, and 5% weight/weight, respectively. The SBS was then assessed using a universal testing machine and antimicrobial activity against Streptococcus mutans were assessed. Statistical analyses, including Kruskal-Wallis and one-way ANOVA tests, were performed. Results. The results showed that among the experimental groups, the 3% concentration of SP oil had the highest average SBS value, closely followed by the control group. In contrast, the SP group with a 5% concentration had the lowest mean shear bond strength values. ANOVA analysis indicated no significant differences either within or between the mean values. Antimicrobial testing revealed a concentration-dependent antibacterial effect, with the 5% concentration group demonstrating the highest efficacy. Conclusion. Orthodontic adhesive modified with SP oil maintains favorable SBS while demonstrating antimicrobial effects against Streptococcus mutans.